Effect of inclination angle on the thermal performance of an ultrathin heat pipe with multi-scale wick structure. (November 2020) - Tang, Heng; Weng, Changxing; Tang, Yong; Lu, Yanjun; Fu, Ting
Abstract: In this study, a multi-scale copper mesh wick structure fabricated by oxidation treatment and sintering is proposed for increasing the heat transport capabilities of ultrathin heat pipes (UTHPs). Experimental apparatus and a thermal resistance network model were established to analyse the heat transfer characteristics of UTHPs. The effects of various heating loads and negative inclination angles on the thermal performance of a UTHP with an oxidised mesh wick (OMHP) were experimentally investigated. The results were compared with those of an untreated mesh wick ultrathin heat pipe (NMHP) and a sintered powder wick ultrathin heat pipe (CPHP). The experimental results demonstrate that the heat transport capabilities of UTHPs with a mesh wick in the horizontal and inclined orientations were enhanced significantly owing to oxidation. The oxidised mesh wick exhibited the same or better capillary performance as the sintered powder wick in inclined orientations. Moreover, when the inclination angle increased to 90°, the temperature difference of OMHP was 36.4% and 26% lower than that of OMHP and CPHP, respectively, under the input power of 14 W. The thermal resistances of OMHP were lower than those of NMHP (by approximately 57%) and CPHP under identical test conditions.